Kualitas Layanan, Kualitas Produk, dan Kepercayaan Pelanggan terhadap Keputusan Pembelian Gen Z pada Aplikasi Shopee di Kota Surakarta - Nura Amira; Refi Ayu Radia; Nazla Asyifah Tribuana; Andrea Khoirunnisa Wibisono; Ardelia Putri Tamara (Universitas Muhammadiyah Surakarta, 2025)
This study aims to analyze the effect of service quality, product quality, and customer trust on purchasing decisions on the Shopee e-commerce platform. This research uses a quantitative approachwith purposive sampling to determine the sample of respondents consisting of Shopee consumers in Surakarta. Data were collected through questionnairesdistributed to 150 respondents and analyzed using EViews software to test the hypotheses using multiple linear regression. The results indicate that servicequality, product quality, and customer trust have a positive and significant effect on purchasing decisions. Specifically, good service quality, such as quick responses, timely delivery, and effective customerservice, has a significant positive impact on purchasing decisions. Additionally, the product quality sold on Shopee, which can be assessed through reviews and ratings, also contributes to the improvement ofpurchasing decisions. Customer trust in products and the e-commerce platform, particularly regarding product authenticity and transaction security, influences purchasing decisions. The results of thecoefficient of determination test show an R-squared value of 0.819692 and an Adjusted R-squared value of 0.814058, meaning that the regression model explains approximately 81.97% of the variation in purchasing decisions. This study contributes significantly tounderstanding the factors influencing consumer behavior on e-commerce platforms, with a recommendation for future research to consider othervariables that may further clarify the factors affecting purchasing decisions.